Understanding the concept of al-ibtila’ (trial) in personality development: the Muslim flood victims’ experience - Naim, M. Khairul; Hilmi, Syed M.; S., Che Zarrina; S., Nurul Salikin; M. Hambali, Khadijah; Adli, Wan; Z. Abidin, Azmil; Mamat, M. Anuar; Borhan, Joni T.; A. Latif, Faizuri; Saged, Ali G.; Azhar, M. Hazim; et al. (2016)
Religious coping plays an important role to rehabilitate victims affected by traumatic life events. Islamic teachings emphasizes al-ibtila' (trial) concept that serves in understanding the concept of qada’ (fate) and qadar (destiny).This study explored al-ibtila’ in coping with traumatic events by achieving sense of personal control in situations that produce distress and torment, as exhibited by 2014 flood victims in Temerloh, Pahang.This study analyzed their understanding, genuine acceptance, and relationship between understanding of al-ibtila' and personality development in overcoming trauma. A mixed-method approach was applied, comprising methods of documentation, interviews (five interview subjects selected by sequential sampling), and survey questionnaires (300 flood victims as respondents). Data from documentation and interviews were analyzed using the inductive approach (qualitative) in a descriptive study, while survey data were analyzed using descriptive and inferential statistical tests (quantitative). The findings gave evidence of significant positive effects in dealing with flood disaster stress from three aspects: the understanding, acceptance, and relationship between understanding of al-ibtila' with good personality development.These results emphasized the need to include understanding and acceptance of al-ibtila' as part of God’s plan in the face of traumatic events, indicating that highly optimistic flood victims can positively deal with traumatic events.